Historical linguistics 2019: selected papers from the 24th International Conference on Historical Linguistics, Canberra, 1-5 July 2019 - Evans, Bethwyn; Gallego, Maria Kristina; Miceli, Luisa (Amsterdam studies in the theory and history of linguistic science, 2024)
"This volume comprises a selection of papers that were presented at the 24th International Conference on Historical Linguistics (ICHL24), which took place at the Australian National University (ANU) in Canberra from 1-5 July, 2019. The volume's aim is to reflect the breadth of research presented at the conference, with each chapter representative of a workshop or themed session. A striking aspect of ICHL24 was the three-day workshop on computational and quantitative approaches to historical linguistics and two of the chapters represent different aspects of this workshop. A number of chapters present research that explores mechanisms and processes of change within specific domains of language, while others explore interactions of change across linguistic domains. Two chapters represent a common theme at the conference and consider the role of historical linguistics in explaining non-linguistic histories of language diversification"--
Includes bibliographical references and index
Keywords: Konferenzschrift -- 2019 -- Canberra; Historische Sprachwissenschaft